Analisis Rasio Likuiditas Dan Profitabilitas Untuk Menilai Kinerja Keuangan Pada Kpn Wiyata - Putu Eka Nopiyani (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2021)
This study aims to analyze and assess financial performance based on liquidity ratios, and profitability ratios at the Wiyata Civil Service Cooperative (KPN Wiyata). The subject of this research is the financial statements of KPN Wiyata for the period 2018-2020. Data collected with secondary data. While the analysis used is descriptive quantitative using ratio analysis based on the Regulation of the State Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia, number 06/Per/M.KUKM/V/2006 dated May 1, 2006 concerning Guidelines for Assessment of Cooperatives with Achievements/Cooperative Award. The results of this study indicate that (1) based on the liquidity ratio of KPN Wiyata for three years, it is included in the bad criteria. (2) based on the profitability ratio seen from the return on assets for three years, it is included in the criteria of quite good and good.